Ethics in International Practice. - Davis-McFarland, Elise (Perspectives of the ASHA Special Interest Groups, 2020)
Purpose: Credible information on the numbers of people in Majority World countries who have communication and swallowing disorders does not seem to exist; however, there is evidence of the need for communication therapy services in those countries. Certified speech-language pathologists who provide clinical services for people with communication and swallowing disorders overseas must adhere to the American Speech-Language-Hearing Association's Code of Ethics. The purpose of this article is to discuss the requirements for the exercise of autonomy, beneficence, nonmaleficence, and justice in the context of international practices. Method: The relationship between cultural authenticity and ethically provided services is considered. There is also a discussion of the ethics and outcomes of short-term volunteer programs for clients in Majority World countries and communities. Guidance for development of needed services and programs in the Majority World is offered. Examples of culturally relevant and ethically developed service and collaboration projects are cited. Results: The codes of ethics of several Minority and Majority World speech-language therapy associations are reviewed to reflect their requirements for the ethical practices that must be adhered to during clinical practice beyond their members' national borders. There is also guidance on the importance and influence of clinicians' attitudes and demeanor in their work in Majority World countries. Conclusions: Ethical clinical practice in Majority World countries requires adherence to the clinician's professional association's code of ethics. Equally important are information and attitudes that enable the clinician to develop and provide services from a perspective of cultural humility and understanding of the community's attitudes, needs, and expectations. An important and necessary aspect of ethical practice is the clinician's personal attitudes and knowledge of the country they bring to their clinical practice.